2012
DOI: 10.1073/pnas.1201310109
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of human allele-specific DNA methylation

Abstract: DNA methylation mediates imprinted gene expression by passing an epigenomic state across generations and differentially marking specific regulatory regions on maternal and paternal alleles. Imprinting has been tied to the evolution of the placenta in mammals and defects of imprinting have been associated with human diseases. Although recent advances in genome sequencing have revolutionized the study of DNA methylation, existing methylome data remain largely untapped in the study of imprinting. We present a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 44 publications
3
123
1
Order By: Relevance
“…Notably, we found that one ASM region located within the promoter of ZNF718 was also common to all 9 tissues. Although conclusive experimental data are not available for characterizing ZNF718 as an imprinting gene, our findings agree with those of a statistical model developed by Fang et al., which identified ZNF718 as a candidate imprinting gene 22 . Nevertheless, our results demonstrate that Q-RRBS can be used to accurately identify ASM regions by using UMIs.…”
Section: Q-rrbs Can Be Used To Identify Asms In the Absence Of Heterosupporting
confidence: 93%
“…Notably, we found that one ASM region located within the promoter of ZNF718 was also common to all 9 tissues. Although conclusive experimental data are not available for characterizing ZNF718 as an imprinting gene, our findings agree with those of a statistical model developed by Fang et al., which identified ZNF718 as a candidate imprinting gene 22 . Nevertheless, our results demonstrate that Q-RRBS can be used to accurately identify ASM regions by using UMIs.…”
Section: Q-rrbs Can Be Used To Identify Asms In the Absence Of Heterosupporting
confidence: 93%
“…DNA methylation is an important epigenetic mark controlling gene expression, thus playing pivotal roles in many cellular processes including embryonic development [1], genomic imprinting [2,3], X-chromosome inactivation [4], transposable element repression [5], and preservation of chromosome stability [6]. Aberrant DNA methylations are known to be associated with human diseases such as cancers, lupus, muscular dystrophy, and imprintingrelated birth defects [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Another open problem in the analysis of single-cell methylation data is the resolution (known as phasing) of epi-haplotypes to allow recovery of a single-chromosome methylome in diploid cells 44 . Phasing can be important for physically linking the methylation state of promoters, regulatory elements and transcribed units in cis.…”
Section: Lamina-associated Domainsmentioning
confidence: 99%